with or without light? reflections on the etymology of the word student (Revista Electrónica REDINE, 2018)
The following essay about the etymology of the word “Alumno” is based on a complete, rigorous and reflexive investigation focused on a documental study. Also, it has as a main purpose to expose the origin and the evolution of such a word through a diachronic pass in order to clarify the doubts generated by its connotation. This is confronted with an elemental opposition: positive or negative. For this reason, the ideas which are presented try to make clear the positive sense that the word “alumno” has, denying that supposition based on just simple speculations: a lumen: sin luz. It is important to mention that the essay begins with a brief exposition of the word “Alumno”, and then, it answers four important questions, such as: Is it from Greek? Does it come from Latin? Is it composed by a meaning sin, and lumen meaning luz? Are there proves that explain its positive connotation? These questions are answered in order to clarify each idea, taking into consideration arguments and reflections, avoiding wrong and speculative judgments.
Keywords: etymology; connotation; evolution; alumno